Electrodeposition of Poly(3,4-ethylenedioxythiophene) @Ni(OH)2 hybrid material on carbon microfibres for ammonia oxidation in alkaline media - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
Ammonia oxidation reaction (AOR) is an intriguing field of research with significant potential to address global energy challenges and advance a greener, more sustainable future by harnessing its role as a renewable energy source. In this study, we present a hybrid platform composed of carbon microfibres that have been modified with poly(3,4-ethylenedioxythiophene) and nickel hydroxide/oxyhydroxide (CP/PEDOT@Ni(OH)(2). Morphological and spectroscopic analyses (SEM-EDS, XPS, and FTIR-ATR) confirmed that the PEDOT film uniformly surrounds the carbon microfibre, creating a surface platform suitable for electrodepositing Ni species. The electrochemical parameters that were ascertained included the surface coverage of Ni active species (Gamma(0)* = 1.77 nmol<middle dot>cm(-2)), the electrochemically active surface area (EASA = 113.3 cm(2)), the electron transfer coefficient (alpha = 0.32), and the heterogeneous electron transfer rate constant (k(s) = 16.68 s(-1)). Electrochemical evaluation for AOR revealed that CP/PEDOT@Ni(OH)(2) exhibits a Tafel slope of similar to 30 mV<middle dot>dec(-1), confirming enhanced charge transfer properties. Electrochemical impedance spectroscopy (EIS) revealed a decline in capacitance and charge-transfer resistance in the presence of ammonia, suggesting the presence of active sites for charge storage and transfer, which are controlled by the diffusion process at the PEDOT@Ni(OH)(2)/solution interface. These findings underscore the synergistic contribution of PEDOT and Ni oxyhydroxide in facilitating electron and ion transport, thereby establishing CP/PEDOT@Ni(OH)(2) as a promising anode electrocatalyst for low-temperature direct ammonia fuel cells.